Foreign exchange speculation: An event study - Rob Hayward (International Journal of Financial Studies, 2018)
Does speculation facilitate price discovery or instability? If it is price discovery, it is beneficial and should be encouraged; if it is instability, welfare is enhanced by its reduction. This paper seeks to distinguish between these two characteristics by analysing those times when speculation in the foreign exchange market is most extreme. A series of event studies are conducted on the extremes of speculative sentiment and speculative activity. If speculation is noise, extreme sentiment and extreme positions should lead to overshooting and increase risk of subsequent reversals. The finding that speculative extremes do not provide information about subsequent returns implies that speculation is part of the process of price discovery and that efforts to reduce it would reduce the informational efficiency of financial markets.
Keywords: 330; foreign exchange; speculation; event-study